2019
DOI: 10.3168/jds.2019-16562
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic 1-carbon metabolism enzyme activity, intermediate metabolites, and growth in neonatal Holstein dairy calves are altered by maternal supply of methionine during late pregnancy

Abstract: Maternal supply of methyl donors such as methionine (Met) during late pregnancy can affect offspring growth and development. The objective was to investigate the effect of postruminal Met supply during late pregnancy on 1-carbon, Met cycle, and transsulfuration pathways in the calf liver. During the last 28 d of pregnancy, cows were individually fed a control diet or the control diet plus rumen-protected dl-Met (MET; 0.09% dry matter intake). Liver samples obtained from calves (n = 14/group) at 4, 14, 28, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Xue and Snoswell [77] observed that hepatic BHMT activity in lambs increased with age until a ruminant state was reached, whereas MTR activity had a pattern that was opposite to BHMT. In dairy calves, a similar response was observed with BHMT activity increasing between 4 and 14 d of age and decreasing between 28 and 50 d of age [78,79]. The changes in activity over time in pre-ruminants are likely linked to the establishment of a functional ruminal microbiome, which leads to increased vitamin B 12 biosynthesis, a cofactor of MTR.…”
Section: Characteristics Of One-carbon Metabolism Pathways In Calvesmentioning
confidence: 62%
“…Xue and Snoswell [77] observed that hepatic BHMT activity in lambs increased with age until a ruminant state was reached, whereas MTR activity had a pattern that was opposite to BHMT. In dairy calves, a similar response was observed with BHMT activity increasing between 4 and 14 d of age and decreasing between 28 and 50 d of age [78,79]. The changes in activity over time in pre-ruminants are likely linked to the establishment of a functional ruminal microbiome, which leads to increased vitamin B 12 biosynthesis, a cofactor of MTR.…”
Section: Characteristics Of One-carbon Metabolism Pathways In Calvesmentioning
confidence: 62%
“…Throughout the preweaning period, calves born to dams supplemented with RPM during late gestation had greater in vitro neutrophil phagocytosis, suggesting a priming effect of maternal Met supplementation on calf immune function ( Alharthi et al, 2019b ). Maternal Met supply also increased the hepatic activity of CBS and the concentrations of taurine compared with control calves, suggesting a greater flux of the transsulfuration pathways and a better antioxidant response with maternal Met supply ( Alharthi et al, 2019a ). Additionally, in another study, maternal Met supply during late gestation led to lower expression of TNF-α and MPO in PMNL at birth, while TLR2 , NOS 2, and cell adhesion molecule 1 were lower throughout the preweaning period ( Jacometo et al, 2018 ).…”
Section: Aa and Dairy Calvesmentioning
confidence: 99%
“…For instance, several studies with dietary methyl donors (e.g., methionine, choline, and folic acid) in peripartal dairy cows have confirmed benefits in performance, health, and immune function (Graulet et al, 2007;Osorio et al, 2013a;Vailati-Riboni et al, 2017b;Arshad et al, 2020). Many of these benefits were also linked to positive responses on aspects of energy metabolism, inflammation, antioxidant status, and birth BW in the offspring (Jacometo et al, 2016;Alharthi et al, 2019a;Duplessis and Girard, 2019), underscoring that adequate supply of methyl donors during later stages of fetal life is an important determinant of immunocompetence and growth in the neonatal calf (Alharthi et al, 2018(Alharthi et al, , 2019bZenobi et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…From a physiological point of view, increased supply of FOA and cobalt, the latter by enhancing B 12 ruminal synthesis, could lead to greater endogenous Met synthesis (i.e., remethylation; Xue and Snoswell, 1985a,b). Although isolated effects of maternal supplementation with methyl donors during early postnatal life have already been demonstrated (Jacometo et al, 2016(Jacometo et al, , 2017(Jacometo et al, , 2018Abdelmegeid et al, 2017;Alharthi et al, 2018Alharthi et al, , 2019a, it remains to be determined whether increased supply of FOA and B 12 , through increased cobalt supply, alone or combined with Met, generate similar effects in neonatal innate immune responses.…”
Section: Introductionmentioning
confidence: 99%